2009
DOI: 10.1113/jphysiol.2009.176461
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of oxytocin and natriuretic peptides in diabetes: possible implications in cardiomyopathy

Abstract: Regular physical activity is beneficial in preventing the risk of cardiovascular complications of diabetes. Recent studies showed a cardioprotective role of oxytocin (OT) to induce natriuretic peptides (NPs) and nitric oxide (NO) release. It is not known if the diabetic state is associated with a reduced OT-NPs-NO system and if exercise training improves this system. To address this, we investigated the effects of treadmill running using the db/db mouse model of type 2 diabetes. Eight-week-old db/db mice were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
46
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 52 publications
8
46
0
Order By: Relevance
“…The contribution of this system to the development of diabetic cardiomyopathy is indicated by the fact that chronic administration of OT and BNP prevented cardiac dysfunction and heart remodeling naturally developing in the db/db mice 30,31. We have demonstrated that ET improves expression of the OT–NP system in ovariectomized rats32 but fails to reverse most components of this cardioprotective system in the diabetic mouse 28,33. It is unknown to what extent the development of cardiomyopathy in exercised db/db mice is associated with binge eating that is common in the diabetic db/db mouse 34.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…The contribution of this system to the development of diabetic cardiomyopathy is indicated by the fact that chronic administration of OT and BNP prevented cardiac dysfunction and heart remodeling naturally developing in the db/db mice 30,31. We have demonstrated that ET improves expression of the OT–NP system in ovariectomized rats32 but fails to reverse most components of this cardioprotective system in the diabetic mouse 28,33. It is unknown to what extent the development of cardiomyopathy in exercised db/db mice is associated with binge eating that is common in the diabetic db/db mouse 34.…”
Section: Introductionmentioning
confidence: 77%
“…In heart, OT exerts direct cardioprotection through the OT receptor (OTR), or indirectly via the stimulation of natriuretic peptides (NPs; atrial NP [ANP], brain NP [BNP], and C-type) and nitric oxide (NO) synthesis 26,27. This functional OT–NP–NO system is downregulated in hearts from db/db mice 28,29. The contribution of this system to the development of diabetic cardiomyopathy is indicated by the fact that chronic administration of OT and BNP prevented cardiac dysfunction and heart remodeling naturally developing in the db/db mice 30,31.…”
Section: Introductionmentioning
confidence: 99%
“…In such affection, fibrosis affects several organs including kidney, liver, heart or the adipose tissue, and its intensity is negatively correlated with the degree of insulin-sensitivity [108][109][110][111][112]. Our group has shown an overproduction of LPA in kidney and adipose tissue from insulin-resistant obese individuals resulting from an over-expression of the LPA-producing enzyme autotaxin [113,114].…”
Section: Expert Opinion and Conclusionmentioning
confidence: 86%
“…Regular exercise can prevent the progression of diabetes-related complications and improve overall cardiovascular health. Based on the results of exercise-based studies glucose control is not achieved in the obese diabetic db/db mouse [25,26,[51][52][53][54]. This should not raise any doubts regarding the suitably of this model for training studies, because benefits on other cardiovascular risk factors have been reported.…”
Section: Discussionmentioning
confidence: 99%